Wireless power transfer to a micro implant device from outside of human body - Kazuya Yamaguchi; Kazuma Onishi; Kenichi Iida (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper states wireless power transfer (WPT) from an AC power supply to a micro implant device in human body. At first, an equivalent circuit of WPT which contains biomedical tissue is constructed with an AC power supply, parasitic components, load resistance, and inductances. Then a state equation which stands for the behavior of circuit is found, and the expression of efficiency is derived as the ratio of the power of power supply and load. Finally an experiment is conducted based on the theoretical calculation, and the error between experimental and calculated result is computed and examined.